BSA-dextran emulsion for protection and oral delivery of curcumin. (December 2016) - Wang, Chaonan; Liu, Zhijia; Xu, Guangrui; Yin, Baoru; Yao, Ping
Abstract: In this study, BSA-dextran conjugate, produced by Maillard reaction, was used as emulsifier and stabilizer to produce curcumin-loaded oil in water emulsions. At fixed pH and BSA-dextran concentration in aqueous phase, the increases of curcumin concentration in oil phase from 12 to 15 mg/mL and oil volume fraction from 20% to 40% did not influence curcumin loading efficiency, but the oil-water interfacial films became imperfect, which were observed by transmission electron microscopy. The emulsion with integrated and cross-linked interfacial film formed on a heat treatment was long-term stable at various temperature and pH conditions, including physical stability of the emulsion and chemical stability of the loaded curcumin. Ex vivo fluorescence images of mice by means of hydrophobic fluorescence probe-loaded BSA-dextran emulsion revealed that the emulsion and/or released probe were mainly in gastrointestinal tract after oral administration and almost disappeared at 24 h post-administration. The pharmacokinetics analysis demonstrated that curcumin-loaded BSA-dextran emulsion could increase curcumin oral bioavailability in mice by 4.8-fold compared with curcumin/Tween 20 suspension. This study verifies that the emulsion can protect loaded curcumin from decomposition and also can promote curcumin absorption in gastrointestinal tract, indicating that protein-polysaccharide emulsions are good oral delivery systems for hydrophobic drugs and nutrients. Graphical abstract: Highlights: BSA-dextran conjugate was produced by Maillard reaction. Curcumin-loaded emulsions were produced using BSA-dextran as the emulsifier. The emulsion with integrated and crosslinked interfacial film is long-term stable. The emulsion can protect curcumin from decomposition at various conditions. The emulsion can greatly increase curcumin oral bioavailability.